A Strategic roadmap to nanotechnology & advances in catalysis in Malaysia - Hamid, Sharifah Bee Abd (2007)
The birth of Nano-technology has affected and became a way to solve many problems in human being life. There are many applications of nanotechnology have been applied and improved quality of human's life. The winner in the global competition is who leads in the nanotechnology and integrates all of the science and technology aspects. Indonesia should take a part of this prospect area to compete in the global era. In the present report, status of research and development on nanotechnology in Indonesia is described. The brief historical development of research on nanotechnology in Indonesia is reported first. The program of the State Ministry of Research and Technology in supporting the research and development of nanotechnology in Indonesia then described. Professional association (Indonesian Society of Nanotechnology, MNI: Masyarakat Nanoteknologi Indonesia) activities are also explained. Finally, the several current progress of researches and developments on nanotechnology in Indonesia and their challenges are described.